CONTEMPORARY TRENDS IN LIFELONG LEARNING. A NIGERIA PERSPECTIVE - Ohuoha, Maudaline Ifeoma (Journal of Continuing and Development Education, 2022)
This paper examined lifelong learning Nigerian perspective. It begins with x-ray of various definitions of lifelong learning by scholars. Lifelong learning recognizes that learning is not confined to childhood or the classroom but takes place throughout life and in a variety of situations. Traditional education in Nigeria as they relate to local customs are practices. The various aspect of lifelong learning such as: informal learning, self-motivated learning, self-funded learning and universal participation are explored and related to the collective, social and economic problems. The idea is to provide some lessons for Nigerian aspect of lifelong learning managers as well as expose them to issues and challenges confronting lifelong learning in our part of the globe. The structure of job has been changing during the passing process from industrial society to the information society. The workers need to learn new things and improve themselves to have new skills. The global competition.